2019
DOI: 10.1007/s10439-019-02403-0
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative and Resorbable PLA/HA Hybrid Construct for Tendon/Ligament Tissue Engineering

Abstract: Tendon and ligament shows extremely limited endogenous regenerative capacity. Current treatments are based on the replacement and or augmentation of the injured tissue but the repaired tissue rarely achieve functionality equal to that of the preinjured tissue. To address this challenge, tissue engineering has emerged as a promising strategy. This study develops a regenerative and resorbable hybrid construct for tendon and ligament engineering. The construct is made up by a hollow poly-lactic acid braid with em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Although compromised by the side effects of acidic degradation products, PGA, PLA and their copolymer PLGA are favorable polymers that are widely applied in tissue engineering because of their biocompatibility, biodegradability, good mechanical properties and excellent processability ( Araque-Monrós et al, 2020 ; Mao et al, 2021 ). PLGA is the most frequently used applications of PLA and PGA in tendon tissue engineering has by the properties of excellent biocompatibility and tunable mechanical and degradation properties.…”
Section: Strategies Involving Scaffolds For Tendon Tissue Engineeringmentioning
confidence: 99%
“…Although compromised by the side effects of acidic degradation products, PGA, PLA and their copolymer PLGA are favorable polymers that are widely applied in tissue engineering because of their biocompatibility, biodegradability, good mechanical properties and excellent processability ( Araque-Monrós et al, 2020 ; Mao et al, 2021 ). PLGA is the most frequently used applications of PLA and PGA in tendon tissue engineering has by the properties of excellent biocompatibility and tunable mechanical and degradation properties.…”
Section: Strategies Involving Scaffolds For Tendon Tissue Engineeringmentioning
confidence: 99%
“…It has been demonstrated that textile structures have enhanced mechanical properties and can mimic natural structures by providing a wide range of fiber forms and pore sizes (Saveh-Shemshaki et al, 2019;Ouyang et al, 2002;Chen et al, 2012). Textile-based scaffolds, such as knit, braid, and woven (Jiang et al, 2021) (Figure 4), have the potential to mimic the mechanical properties of natural tendons, overcoming the limitations of nanofibrous scaffolds, and are used in many tendon regeneration studies (Zhang et al, 2015b;Wu et al, 2017b;Cai et al, 2018a;Araque-Monrós et al, 2020;Han et al, 2021). One strategy is to create multiscale nanofibrous textile-based scaffolds using strands or yarns of nanofibers (Almeida et al, 2019;Chen et al, 2021d;Ma et al, 2022).…”
Section: Multiscale Nanofibrous Scaffoldsmentioning
confidence: 99%
“…The rate of degradation determines its usage. For example, polymers with a low degradation rate, such as PCL, are suitable for building longer-term tendon scaffolds ( Laranjeira et al, 2017 ; Calejo et al, 2019 ), while polymers with faster degradation rates are less suitable since they may increase the inflammation response, including PLA, PGA, and PLGA ( Yokoya et al, 2008 ; Vuornos et al, 2016 ; Chen et al, 2019 ; Chen P. et al, 2020 ; Araque-Monrós et al, 2020 ; El Khatib et al, 2020 ). According to this characteristic, a PEG-based hydrogel system with a range of degradation rates can control the timing of MSC delivery to the target site of tendinopathy ( Qiu et al, 2011 ).…”
Section: Biomaterialsmentioning
confidence: 99%